A Nonflammable and Thermally Stable Polyethylene/Glass Fiber−Magnesium Hydroxide/Polyethylene Composite Separator with High Mechanical Strength and Electrolyte Retention to Enhance the Performance of Lithium‐Ion Batteries. Issue 3 (22nd January 2022) - Chen, Jiahui; Kang, Tianxing; Cui, Yan; Zhao, Jingyang; Xue, Jianjun; Xu, Hanliang; Nan, Junmin
Abstract : To overcome the shortcomings in the thermal stability and electrolyte wettability when a commercial polyethylene (PE) separator is used alone, a PE/glass fiber (GF)−Mg(OH)2 /PE composite (PGMP) separator is developed, and the electrochemical and safety performance of lithium‐ion batteries is effectively enhanced. The PGMP separator is prepared by soaking a mixed dispersion solution of polyacrylate and Mg(OH)2 into the GF fabric substrate and subsequently bonding the PE microporous film on both substrate sides. Compared with the PE separator, PGMP separator exhibits enhanced mechanical strength (≥250 MPa), ionic conductivity, and electrolyte wettability. Furthermore, there is almost no shrinkage when this PGMP is annealed at 350 °C for 30 min. The nail penetration, impact, overcharge, and adiabatic rate calorimeter tests of LiNi0.5 Co0.2 Mn0.3 O2 /graphite pouch cell with a nominal capacity of 2500 mAh show that the PGMP separator effectively improves the safety performance. The thermal runaway temperature of the pouch cells is increased from about 120 to 146 °C, and the electrolyte wettability ability of the PGMP separator gives the cell a capacity retention of 85% after 500 cycles at 1.0 C. Combined with the advantages, it is indicated that this PGMP separator has great potential in commercial applications. Abstract : The self‐supporting layer composed of glass fiber (GF) fabric and Mg(OH)2 has the characteristics of nonflammability, thermal stability, high strength, and electrolyte retention, which effectively improve the high temperature resistance and related physical and chemical properties of the polyethylene/GF‐Mg(OH)2/PE composite separator and effectively improve the safety and electrochemical performance of the pouch cell.